An in situ postexposure feeding assay with Carcinus maenas for estuarine sediment-overlying water toxicity evaluations - Moreira, Susana M. (2006)
This study developed and evaluated a short-term sublethal in situ toxicity assay for estuarine sediment-overlying waters, with the crab Carcinus maenas (L.) based on postexposure feeding. It consisted of a 48-h in situ exposure period followed by a short postexposure feeding period (30 min). A precise method for quantifying feeding, using the Polychaeta Hediste (Nereis) diversicolor Müller as food source, was first developed. The sensitivity of the postexposure feeding response was verified by comparing it to that of lethality, upon cadmium exposure. The influence of environmental conditions prevailing during exposure (salinity, temperature, substrate, light regime, and food availability) on postexposure feeding was also addressed. The potential of this in situ assay was then investigated by deploying organisms at ten sites, located in reference and contaminated Portuguese estuaries. Organism recovery ranged between 90% and 100% and a significant postexposure feeding depression (16.3-72.7%) was observed at all contaminated sites relatively to references.